Y - (-4) = (5 - (-4))/(2 - (-1)) (x - (-1))
y + 4 = (5 + 4)/(2 + 1) (x + 1)
y + 4 = 9/3 (x + 1)
y + 4 = 3(x + 1)
y + 4 = 3x + 3
y = 3x + 3 - 4
y = 3x - 1
You can start with the form
∆y(x -x1) -∆x(y -y1) = 0
Here, we have
∆y = 11-(-3) = 14
∆x = -3-1 = -4
and we can choose (x1, y1) = (1, -3). This gives
14(x -1) -(-4)(y -(-3)) = 0
14x +4y -2 = 0
All these terms have a common factor of 2 that we can remove. Adding 1 to the result puts it in standard form:
7x +2y = 1
You need to d to one side of the equation by itself and them use PEMDAS to solve your answer
answer:spot-less
Step-by-step explanation:
21.00 divided by 4 is 5.25 so you'd be payingmore at "no mess or stress dry"
-5x
The basic formula for slope of a line is
y = mx + b
where m is the coefficient of x and the slope.
Your equation is already in the right formula. The number there is -5x as your slope. Good luck!